Evaluation of Green Open Space (RTH) Policy in Makassar City - Ayu Lestari; Andi Cudai Nur (Universitas Negeri Makassar, 2021)
This study aims to find out about the Evaluation of Green Open Space (RTH) Policies in Makassar City. using the type of qualitative research that is descriptive and data collection techniques are carried out by interviews, observation and documentation. The data analysis technique used consisted of data collection, data reduction, data presentation, and conclusions. The results showed that the evaluation of green open space policies in Makassar City was seen from the five criteria for evaluating Leo Agustino's policies, namely: 1) apparatus resources 2) institutional 3) facilities and infrastructure 4) financial 5) regulation. Based on the research results, two of the five policy evaluation criteria, namely institutions and regulations, have been implemented properly. However, the criteria for personnel resources, facilities and infrastructure, as well as finance have been implemented but have not been maximized.